2009
DOI: 10.1002/bio.1138
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the long‐persistence phosphor CaAl2O4:Eu2+, Dy3+, Nd3+ by combustion method and its luminescent properties

Abstract: Calcium aluminate phosphor co-doped Eu(2+), Dy(3+), Nd(3+) is prepared by the combustion method. We study systemically the influences of the quantity of mixed Dy(3+) ion, the quantity of flux H(3)BO(3), the differences in dispersing methods between magnetic stirring and ultrasonic dispersing and the combustion temperature on the long-persistence phosphor. The analytical results indicate that Dy(3+) ion improves the properties of the phosphors CaAl(2)O(4):Eu(2+), Nd(3+). The appropriate quantity of flux H(3)BO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, HPMC@NH 2 -CAO and HPMC-FITC 0.4030 @NH 2 -CAO fluorescent films had a transition to high temperature when the mass loss was 50%, and their carbon residues were 43.54 and 43.02% at 600 °C, respectively, which were higher than those of HPMC (8.71%) and HPMC-FITC 0.4030 (11.53%). This was mainly because the addition of NH 2 -CAO made by high-temperature sintering inhibited the heat transfer process, thus conferring good thermal stability to the fluorescent films. , The thermal performance test showed that the fluorescent film could withstand a much higher degradation temperature than the typical application temperature, meaning that HPMC-based dual-emitting films could be used over a wide temperature range of at least 0–120 °C and fully met the needs of light-emitting devices and other electronic devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HPMC@NH 2 -CAO and HPMC-FITC 0.4030 @NH 2 -CAO fluorescent films had a transition to high temperature when the mass loss was 50%, and their carbon residues were 43.54 and 43.02% at 600 °C, respectively, which were higher than those of HPMC (8.71%) and HPMC-FITC 0.4030 (11.53%). This was mainly because the addition of NH 2 -CAO made by high-temperature sintering inhibited the heat transfer process, thus conferring good thermal stability to the fluorescent films. , The thermal performance test showed that the fluorescent film could withstand a much higher degradation temperature than the typical application temperature, meaning that HPMC-based dual-emitting films could be used over a wide temperature range of at least 0–120 °C and fully met the needs of light-emitting devices and other electronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…This was mainly because the addition of NH 2 -CAO made by high-temperature sintering inhibited the heat transfer process, thus conferring good thermal stability to the fluorescent films. 52,53 The thermal performance test showed that the fluorescent film could withstand a much higher degradation temperature than the typical application temperature, meaning that HPMC-based dual-emitting films could be used over a wide temperature range of at least 0−120 °C and fully met the needs of lightemitting devices and other electronic devices.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To resolve this, substituting Si 4+ for Al 3+ has been suggested to provide a larger space at the Ca/Y sites to accommodate Eu 2+ ions [20]. It has also been reported that changing the ratio of Y 3+ to Al 3+ leads to the activation of Eu 2+ emission [21], whose idea is based on the Eu 2+ emission hosted by CaAl 2 O 4 [22,23]. Such composition engineering, including chemical substitution, is a basic approach to designing the luminescence properties of phosphors via adjusting the local environment around luminescent centers; thus, it has been studied in a myriad of phosphors [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, rare earth doped alkaline earth aluminate phosphors have been extensively studied and used in many of applications, such as radiation dosimetry, color display, luminescent porcelain, airport, luminous paints in highway and so on [1][2][3]. This material has strong photoluminescence at the blue region with maximum at 444 nm.…”
Section: Introduction mentioning
confidence: 99%